Analisis Pengaruh Migrasi terhadap Perkembangan Kota Ambon Berdasarkan Sosial Kependudukan - Merti Siska Rosely; Lendra S Pattikawa; Grashella M Nusamara (STIKes Ibnu Sina Ajibarang, 2025)
Urban development can be viewed through the lens of increased socio-economic activities and population mobility flows. Population growth is not solely due to natural increase, but also significantly influenced by migration. Ambon City, the capital of Maluku Province, covers a land area of 359.45 square kilometers, with an additional 17.55 square kilometers of sea area. The substantial influx of migrants into Ambon City presents various challenges, including population density and imbalances in population distribution. This necessitates an investigation into the factors driving migration and its impact on urban development.This research aims to determine the extent of population migration to Ambon City using quantitative descriptive analysis. It analyzes the push and pull factors contributing to migration, utilizing data from population censuses, BPS (Badan Pusat Statistik) data, interviews, and observations to identify migration patterns and their impact on the quality of life for Ambon City residents.The research findings reveal specific details regarding inward migration to Ambon City. However, Ambon City exhibits high rates of both inward and outward migration within Maluku Province. In 2023, Ambon City recorded the highest inward migration rate in Maluku at 27.06% and the highest outward migration rate at 39.71%. Four variables were identified as push factors driving respondents to migrate to Ambon City, and these same four factors were also identified as reasons for migration. The pull factors, represented by these four variables, received strong agreement (agree and strongly agree) from respondents. The research results are expected to provide recommendations for effective policies to manage migration and ensure sustainable and inclusive urban development.